2009
DOI: 10.1002/jmri.21659
|View full text |Cite
|
Sign up to set email alerts
|

T2 detection of tumor invasion within segmented components of glioblastoma multiforme

Abstract: Purpose: To use T2-weighted images to detect tumor invasion when comparing normal individuals to groups of gliomablastoma multiforme (GBM) patients with varying levels of CXCR4, a chemokine receptor that promotes tumor migration.Materials and Methods: T2-weighted images were acquired preoperatively in 22 treatment-naïve GBM patients. Two groups were formed based on the expression levels of CXCR4. A third group of normal volunteers was used for comparison. Each image was segmented to obtain four different clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(61 reference statements)
2
9
0
Order By: Relevance
“…CXCL12 is a known chemokine described in invasion and cell migration and is a ligand of CXCR4, a chemokine receptor that promotes tumor migration and invasion [25], [38], [39], [40]. McMillan et al [25], [38] demonstrated an increased T2-signal intensity in GBM patients with high CXCR4 expression, further corroborating the validity of invasion associated genes in our study. Interestingly, miR-127, the second top downregulated microRNA in the high FLAIR group, was experimentally shown to target CXCL12 [35], [37].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…CXCL12 is a known chemokine described in invasion and cell migration and is a ligand of CXCR4, a chemokine receptor that promotes tumor migration and invasion [25], [38], [39], [40]. McMillan et al [25], [38] demonstrated an increased T2-signal intensity in GBM patients with high CXCR4 expression, further corroborating the validity of invasion associated genes in our study. Interestingly, miR-127, the second top downregulated microRNA in the high FLAIR group, was experimentally shown to target CXCL12 [35], [37].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, miR-219 was significantly downregulated in the Mesenchymal GBM subtype (P<0.0001, Figure 8d) and showed an inverse correlation with POSTN (Rsq = 0.205, Figure 8d) suggesting a potential miR-219-POSTN regulatory mechanism in GBM cellular invasion. Interestingly, the other top downregulated microRNAs in the high FLAIR group, miR-127, was experimentally shown to target CXCL12 mRNA [37], a major factor for GBM invasion [25], [38], [39], [40] and also one of our top genes accounting for high FLAIR volumes (Table 4 and S1). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have shown that histological examination (1)(2)(3)(4)(5)(6)(7)(8) and subsequently diffusion tensor imaging (9)(10)(11)(12)(13)(14)(15)(16)(17) of cerebral peritumoral edema can provide relevant information to deduce the nature of the lesion, metastases or other lesions generating vasogenic edema or tumor-infiltrated edema. However, these results remain either too unreliable to be used in routine radiological practice (16,18,19), or are too complex and purely statistical, preventing simple transposition into clinical practice (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Studies [22,183] demonstrated patients with gliomas of CXCR4 overexpression showed a statistically significant increase in the intensity and extent of peritumoral T2-weighted magnetic resonance imaging (MRI) signal abnormalities. Given the importance of the SDF-1α/CXCR4 signaling in the progress of glioma and poor prognosis of glioma, in the past years, a great deal of effort has been made to develop molecular imaging approaches to noninvasively evaluate SDF-1α or CXCR4 status.…”
Section: Imagingmentioning
confidence: 99%